Generic Super Heroes: Can They Exist? - Aislinn O'Connell (The Comics Grid: Journal of Comics Scholarship, 2020)
The term ‘superhero’ would seem, at first glance, to be generic. That is to say, ‘superhero’ may be a word or term used to refer to any caped, masked or costumed crusader who fights crime, whether super powered, inhuman, demigod, or genius playboy billionaire philanthropist. However, the legalities of super heroes are far more nuanced than that. This article discusses the use of ‘super heroes’ in light of the fact that the term is covered by a trade mark right jointly held by Marvel and DC. It discusses the protection that Marvel and DC maintain over their mark, the impact of this protection, the challenge to the validity of the registration which was heard in 2016, and the possibility of a declaration of genericide, which would allow the term superhero to be freely used.